Design and synthesis of dual cathepsin L and S inhibitors and antimetastatic activity evaluation in pancreatic cancer cells. (15th January 2023) - Huang, Haoqiang; Zhang, Yi; Xu, Xiaohong; Liu, Yongzheng; Zhao, Juanping; Ma, Lili; Lei, Jie; Ge, Wentao; Li, Ning; Ma, Enlong; Li, Yanchun; Yuan, Lei
Graphical abstract: Abstract: Currently, the migration and invasion of cancer cells remain the main factors of poor prognosis in the majority of cancer patients. Developing an effective antimetastatic agent is crucial for cancer therapy. Our recent research revealed that Cat L and S are expressed concurrently in metastatic pancreatic cancer cells. Asperphenamate analog ASPER-29, which exhibits dual Cat L and S inhibitory potency, showed a definite antimetastatic effect on pancreatic cancer BxPC-3 and PANC-1 cells. To further improve the antimetastatic ability of asperphenamate-type molecules, 24 derivatives were designed and synthesized by a scaffold-hopping strategy. The cathepsin inhibitory activity assay results showed that most of the derivatives exhibited dual inhibitory effects on Cat L and S. Among all derivatives, Compound B1a showed the strongest inhibitory activity, with IC50 values of 4.10 ± 0.14 μM and 1.79 ± 0.11 μM, which were 1.5-fold and 2.8-fold more potent than those of positive drugs against Cat L and S, respectively. Further wound-healing and transwell chamber assays demonstrated that B1a presented significant antimetastatic ability in vitro .